New species of the genus Eupithecia (Lepidoptera, Geometridae) from China. Part VIII - Šumpich, Jan; Mironov, Vladimir (Zootaxa, 2022)
In this eighth part of this series, six new species of Eupithecia are described from China: Eupithecia galsworthyi sp. n., Eupithecia fossaria sp. n., Eupithecia eremiata sp. n., Eupithecia panacea sp. n., Eupithecia mediata sp. n. and Eupithecia caementariata sp. n. The species Eupithecia peregovitsi Mironov & Galsworthy, 2009 is presented as new for China. Eupithecia lineisdistincta Vojnits, 1981 and Eupithecia dealbata Inoue, 1988 are recorded from Sichuan Province for the first time. New faunistic data for five additional poorly known species are given, namely for Eupithecia cichisa Prout, 1939, Eupithecia contraria Vojnits, 1983, Eupithecia perendina Vojnits, 1980, Eupithecia nobilitata Staudinger, 1882 and Eupithecia nephelata Staudinger, 1897. Adults and their genitalia are illustrated for all species.